Management of heterotopic ossification affecting both hips and knees. - Devnani, Anand Sobhraj (Singapore Medical Association, 2008)
The management of heterotopic ossification is controversial. This is a rare case affecting both hips and knees of a 22-year-old woman that prevented her from walking. The management and the outcome, three years after excision of the ossific masses, as well as the measures to prevent recurrence after excision of the heterotopic ossification, are discussed.